The Hollow Land - Morris, William, 1834-1896 (Salt Lake City, UT : Project Gutenberg, 2005)
"The Hollow Land" by William Morris is a fantasy novel written in the late 19th century. The book explores themes of love, vengeance, and the longing for an idealized world, focusing on a mythical land where characters strive to find beauty and peace amidst strife and conflict. It reflects Morris's interests in medievalism and romanticism, presenting a narrative that intertwines personal ambition with the allure of a mystical realm. The story follows Florian de Liliis, a young nobleman whose life is intertwined with that of Swanhilda, a vengeful queen. After a series of tragic events driven by revenge against Swanhilda for her treachery, Florian embarks on a quest that ultimately leads him to the Hollow Land$1 (Ba vision of paradise where he hopes to reunite with lost love and find solace. Along the way, Florian grapples with concepts of justice and morality, particularly in regards to his brother, Amald, and the consequences of their violent actions. The narrative culminates in a poignant exploration of love, loss, and the search for redemption in a world filled with both beauty and horror. (This is an automatically generated summary.)s
Release date is 2005-05-31
This eBook was prepared by Andy Robertson
Keywords: Knights and knighthood -- Fiction; Chivalry -- Fiction; Revenge -- Fiction; Atonement -- Fiction; Battles -- Fiction; Purgatory -- Fiction